2018
DOI: 10.11646/phytotaxa.340.3.3
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic account of species in the tribe Spongoclonieae (Ceramiaceae, Ceramiales, Rhodophyta) reported from Atlantic and Pacific Mexico

Abstract: The tribe Spongoclonieae (Ceramiaceae subfam. Spongoclonioideae) is represented on the Atlantic and Pacific coasts of Mexico by two genera: Pleonosporium with eight species and Spongoclonium with a single species. Pleonosporium boergesenii and P. borreri are both new records for Atlantic Mexico. Known in Pacific and Atlantic Mexico, P. rhizoideum has the widest distribution, while P. pygmaeum and P. vancouverianum have only a few records in the study area. Pleonosporium mexicanum is found mainly in tropical Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Plenosporium borreri was reported from the warmer, more southern waters of North Carolina (Williams 1951), but Schneider & Searles (1991) were unable to locate Williams' vouchers of this species. Because of its similarity to P. boergesenii (A.B.Joly) R.E.Norris (Schneider 1975, as Mesothamnion boergesenii Joly), Schneider & Searles (1991) excluded P. borreri from the southeastern U.S. flora, although Mateo-Cid et al (2018) recently reported it from the Atlantic coast of Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Plenosporium borreri was reported from the warmer, more southern waters of North Carolina (Williams 1951), but Schneider & Searles (1991) were unable to locate Williams' vouchers of this species. Because of its similarity to P. boergesenii (A.B.Joly) R.E.Norris (Schneider 1975, as Mesothamnion boergesenii Joly), Schneider & Searles (1991) excluded P. borreri from the southeastern U.S. flora, although Mateo-Cid et al (2018) recently reported it from the Atlantic coast of Mexico.…”
Section: Discussionmentioning
confidence: 99%